2012
DOI: 10.1536/ihj.53.5
|View full text |Cite
|
Sign up to set email alerts
|

Body Surface Two-Dimensional Spectral Map of Atrial Fibrillation Using Vector-Projected 187 Channel Electrocardiography

Abstract: SummaryAtrial cycle length during atrial fibrillation and flutter waves may be correlated with atrial refractoriness and organization. The nature of the frequency by spectral analysis may reflect a profile of atrial cycle length. In this study, we developed a novel body surface 2-dimensional spectral map during fibrillation using vector-projected 187 channel ECG (187ch VP-ECG).The study consisted of 28 patients (24 with atrial fibrillation (AFIB) and 4 atrial flutter (AFL) with valvular heart disease). We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…With regard to vector synthesis high‐resolution ECG indices, X‐Y‐Z lead ECG were averaged and processed through a band‐pass filter (finite impulse response [FIR] type, 45–200 Hz), and filtered QRS (fQRS) was measured in vector magnitude waveforms. The inflection points of the P, QRS, and T waves were determined using differentiation . From lead vectors corresponding to the center electrode and 187 electrodes on the body surface (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to vector synthesis high‐resolution ECG indices, X‐Y‐Z lead ECG were averaged and processed through a band‐pass filter (finite impulse response [FIR] type, 45–200 Hz), and filtered QRS (fQRS) was measured in vector magnitude waveforms. The inflection points of the P, QRS, and T waves were determined using differentiation . From lead vectors corresponding to the center electrode and 187 electrodes on the body surface (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The inflection points of the P, QRS, and T waves were determined using differentiation. [6][7][8]14 From lead vectors corresponding to the center electrode and 187 electrodes on the body surface ( Fig. 1), a 187-channel ECG was synthesized, current density determined, and a "D distribution map of RTc dispersion representing the variation of the repolarization time was prepared ( Fig.…”
Section: Vector Synthesis High-resolution Ecgmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectral analysis of R-R variability was performed, and the sympathetic index was calculated as the ratio of the maximum peak of the high-frequency region (around 0.3 Hz) to the maximum peak of the lowfrequency region (around 0.1 Hz) shown in Figure 1. [7][8][9][10] 187-channel ECG was based on vector-projected theory and was obtained from 187 body surface electrode positions. Two-dimensional repolarization function maps (RTc dispersion maps) were determined from the current density map (Figure 1), and the repolarization index (recovery time (RTc) dispersion and Tpeak-end (Tp-e) dispersion) were determined.…”
Section: Subjectsmentioning
confidence: 99%
“…Nakai, et al reported that markers of abnormal repolarization, such as T wave alternans and RTc dispersion, could be successfully assessed as risk stratification for myocardial injury using a vector-projected 187-channel high-resolution electrocardiograph system (DREAM-ECG). [7][8][9] In this study, we evaluated peripartum myocardial burden in pregnant women using the DREAM-ECG system and serum biochemical markers.…”
mentioning
confidence: 99%